Integration of Human Rights Education in Civic Education Learning Towards Religious Moderation in Students at Universitas Amir Hamzah - Istiawati, Sri; Elisa, Nufaris; Rahmadany; Noor, Maria (Universitas Islam Negeri Raden Intan Lampung, 2025)
Human rights violations in universities remain a pressing issue, causing concerns among parents about the loss of comfort and a conducive learning atmosphere. Addressing this challenge requires urgent action to establish a university environment that promotes, nurtures, and advances human rights. Civics education, a mandatory subject in Indonesian schools, plays a central role in shaping students' civic intelligence and fostering democratic values. It also contributes significantly to the development of responsible citizenship. In the context of Indonesia's democratic landscape, which embraces diverse viewpoints and interests, civics education must adapt to address contemporary issues such as human rights and religious moderation. This research uses a qualitative descriptive approach, drawing on references from books and academic journals, to examine how religious moderation can be integrated into civic education. The study highlights that a civic education strategy rooted in religious moderation, enriched with local wisdom, offers students a more meaningful learning experience. By exploring values close to their cultural context, students can better balance their understanding of human rights with the principles of religious moderation. The findings suggest that incorporating religious moderation into civic education enhances students' awareness of human rights, tolerance, and social responsibility.